EKSTRAKSI PROTEIN DARI BUNGKIL INTI SAWIT DENGAN TEKNIK PENGENDAPAN MENGGUNAKAN PELARUT ALKALI (Extraction of Protein from Palm Kernel Cake with Precipitation Method Using Alkaline) - Hasibuan, Hasrul Abdi; Daulay, Anny Sartika (Jurnal Hasil Penelitian Industri, 2015)
Extraction of protein from palm kernel cake (PKC) has been conducted via 2 step i.e. 1)protein was dissolved using akaline solution (NaOH) and 2) protein was separated using precipitationtechnique with added chloride acid (HCl). The research was conducted using Response SurfaceMethodology (RSM) for study the effects of variable interaction includes the ratio of PKC and solvent,temperature and time on extraction to obtaining the optimal of consentrate, yield and recovery. Theresults of RSM analysis shows that the time of extration and temperature had a significant influence onyield of protein while the ratio of PKC and solvent had not significant effect. The condition optimum wasreached at the ratio of PKC and solvent 1:50, temperature 40 Â°C and time 3 hours. At optimumconditions about 46% protein can be extracted from the PKC with 14.6% yield and protein content in theconcentrate of 49.72%. Protein concentrate containing amino acids with the largest component isglutamate 11.04%, aspartate 5.69% and leucine 5.03%.